Fixed point theorems for the Mann's iteration scheme in convex graphical rectangular b-metric spaces. (3rd June 2021) - Chen, Lili; Yang, Ni; Zhao, Yanfeng
Abstract : In this paper, we first introduce the concept of the convex graphical rectangular b -metric space ( G R b C M S ) by means of the convex structure. Moreover, the definitions of G -contraction mappings, G -quasi-contraction mappings, T -Mann sequences and TB -Mann sequences are presented in G R b C M S . Then we obtain strong convergence theorems for these mappings in G R b C M S under some suitable conditions. Furthermore, an example for supporting our main result is shown.